2017
DOI: 10.1021/acs.jpca.7b04344
|View full text |Cite
|
Sign up to set email alerts
|

Coherent Exciton Delocalization in a Two-State DNA-Templated Dye Aggregate System

Abstract: Coherent exciton delocalization in dye aggregate systems gives rise to a variety of intriguing optical phenomena, including J- and H-aggregate behavior and Davydov splitting. Systems that exhibit coherent exciton delocalization at room temperature are of interest for the development of artificial light-harvesting devices, colorimetric detection schemes, and quantum computers. Here, we report on a simple dye system templated by DNA that exhibits tunable optical properties. At low salt and DNA concentrations, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
149
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(157 citation statements)
references
References 101 publications
(181 reference statements)
4
149
0
Order By: Relevance
“…For example, 8 π‐stacked phenanthrenes formed through dsDNA presented 230% AE over direct excitation of a pyrene, though this effect was limited to a ≈2 nm length construct 165a. Within the light‐capture paradigm, dye‐aggregates are of particular interest as their absorbance properties are greatly modified, shifting the absorbance peaks and allowing for greater coverage of broad white‐light spectra . An interesting example of this type was reported by Ensslen et al who demonstrated a dsDNA wire with ethynyl pyrene, ethynyl perylene, and ethynyl nile red dyes incorporated as modified nucleosides.…”
Section: Fluorescently Labeled Dna Materialsmentioning
confidence: 99%
“…For example, 8 π‐stacked phenanthrenes formed through dsDNA presented 230% AE over direct excitation of a pyrene, though this effect was limited to a ≈2 nm length construct 165a. Within the light‐capture paradigm, dye‐aggregates are of particular interest as their absorbance properties are greatly modified, shifting the absorbance peaks and allowing for greater coverage of broad white‐light spectra . An interesting example of this type was reported by Ensslen et al who demonstrated a dsDNA wire with ethynyl pyrene, ethynyl perylene, and ethynyl nile red dyes incorporated as modified nucleosides.…”
Section: Fluorescently Labeled Dna Materialsmentioning
confidence: 99%
“…[19] TheD NA-templated formation of helical stacked aggregates of cationic organic molecules is awell-studied phenomenon. [20,21] It has notably been shown that electronic couplings occurs in H-aggregates (parallel stacking) and J-aggregates (head-to-tail stacking). By analogy with well-studied cationic groove binders such as distamycin, we thus hypothesized that two aplysinopsin molecules could stack head-to-tail with charged groups positioned at opposite ends.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…These findings underscore the diverse requirements for charge and energy delocalization across p-stacked assemblies.Charge and energy dynamics across p-stacked assemblies is of critical importance in biological systems as well in the performance of functional materials. [1][2][3] Va rious p-stacked dimers capable of excimer formation and charge-resonance stabilization based upon benzene, [4][5][6][7][8] fluorene, [9][10][11][12] pyrene, [13,14] and other aromatic donors [15][16][17][18] have served as model systems to gain fundamental insight into key factors controlling charge/energy stabilization. These studies have established that the extent of the cationic charge (that is,hole) and exciton stabilization/delocalization is dependent on the orbital overlap between the chromophores,a nd is optimal when the p-stacked assembly adopts ap erfect sandwich-like arrangement, where orbital overlap and electronic coupling are at their maxima.…”
mentioning
confidence: 99%